2008
DOI: 10.1518/001872008x288295
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Night Vision Goggles on Way-Finding Performance and the Acquisition of Spatial Knowledge

Abstract: These degradations in spatial knowledge should be considered in operational planning and NVG training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 14 publications
2
20
1
Order By: Relevance
“…Gauthier et al [19] reported a recent experiment that complements the findings of the present study. In their study, participants were required to acquire route knowledge and find target objects while navigating a real maze, using unaided vision or when wearing night vision goggles.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Gauthier et al [19] reported a recent experiment that complements the findings of the present study. In their study, participants were required to acquire route knowledge and find target objects while navigating a real maze, using unaided vision or when wearing night vision goggles.…”
Section: Discussionsupporting
confidence: 90%
“…The use of aerial perspective is more relevant to pilotage using NVDs. The studies also differed in that in the Gauthier et al [19] study spatial knowledge was acquired through active exploration, whereas in our study it was gained by passive viewing of the scenes. In addition, the use of real night vision goggles confounded the display format with a restricted field of view.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Gauthier et al (2008) also focused on night visiong goggles and conducted their landmark search experiment indoors in a small artificial maze where they could set the lighting level similar to half moonlight for the goggle group. The control group participated without night vision goggles in full lighting and performed significantly better in the search, direction estimation and map drawing task.…”
Section: Previous Studies On Landmarks and Wayfinding At Nightmentioning
confidence: 99%